REVERSING THE CELL FATE: A REVIEW ON REPROGRAMMING THE CELL INTO PLURIPOTENT STAGE IN THE 21ST CENTURY - MANASH P. BARKATAKI (International Journal of Pharma and Bio Sciences, 2012)
Recent studies in the field of regenerative medicines suggesting the potential benefits of iPS cells have made the scientists to develop novel techniques which can produce iPS cells from terminally differentiated cells. The current review looks into the different factors involved in reprogramming a differentiated cell and also gives a brief overview of different approaches.